PENGARUH UPAH MINIMUM KABUPATEN/KOTA (UMK) TERHADAP PENYERAPAN TENAGA KERJA DI KOTA BUKITTINGGI - Afifah Khairyah; Amsah Hendri Doni (CV. Adiba Aisha Amira, 2025)
The origin of this lesson comes from the incident involving workers in Bukittinggi which showed the disparity between UMK and worker absorption. Data shows that during the period 2014-2023, there were significant fluctuations in the workforce and the number of people working. A drastic spike in open unemployment was identified in 2018 reaching 31,185 people from the previous 4,185 people in 2017. Meanwhile, the UMK also showed an increasing trend from IDR 1,490,000 to IDR 2,742,467 in the same period. This lesson aims to explore UMK on labor absorption in Bukittinggi City. By applying a quantitative approach through simple regression analysis. This lesson shows the UMK with a sig value of 0.000 <0.05, which means that the UMK has a significant influence on labor absorption in Bukittinggi City of 57.5% and more than 42.5% is influenced by other factors. These findings indicate that employment policies need to focus on setting optimal UMK while still taking into account local labor market needs.